A combined analysis of five observational studies evaluating the efficacy and tolerability of bimatoprost/timolol fixed combination in patients with primary open-angle glaucoma or ocular hypertension - Pfennigsdorf S (Dove Medical Press, 2013)
Stefan Pfennigsdorf,1 Leo de Jong,2 Stefan Makk,3 Yvette Fournichot,4 Alain Bron,5 Robert J Morgan-Warren,6 John Maltman6 1Ophthalmology Practice, Polch, Germany; 2Academic Medical Center, University of Amsterdam, Amsterdam, Netherlands; 3Ophthalmology Practice, Graz, Austria; 4Ophthalmology Practice, Schlieren, Switzerland; 5Department of Ophthalmology, University Hospital, Dijon, France; 6Allergan Ltd, Marlow, UK Objective: The aim of this study was to evaluate the safety and efficacy of a fixed combination of bimatoprost 0.03% and timolol (BTFC) in a clinical setting, in a large sample of patients with primary open-angle glaucoma or ocular hypertension and insufficient intraocular pressure (IOP) lowering on prior therapy. Methods: Patient data were combined (n = 5556) from five multicenter, observational, non-controlled, open-label studies throughout Europe. Patients were identified from 830 sites in Austria, France, Germany, The Netherlands, and Switzerland. Assessments were made at baseline, 6 weeks (in Austrian, German and Swiss centers), and 12 weeks in all centers. Results: BTFC lowered mean IOP from baseline by 5.4 mmHg over the 12-week duration of the studies (P < 0.0001). At study entry, 92.9% of patients were receiving another ocular hypotensive medication. In patients with no previous treatment (n = 311), BTFC reduced IOP by -9.1 mmHg, corresponding to a reduction from baseline of 36.4% (P < 0.0001). In patients receiving prior therapy of a prostaglandin analog, a ß-blocker, or a fixed combination, BTFC reduced IOP by a further 24.5%, 25.9%, and 21.4%, respectively. The majority of patients (90.3%) reported no adverse events. The most common adverse events were conjunctival hyperemia (3.2%) and eye irritation (2.8%). BTFC was rated as "good" or "very good" by 92.5% of physicians and 88.0% of patients. Most patients (96.3%) were equally or more compliant with BTFC than with their previous treatment. Conclusion: In routine clinical practice, BTFC achieved consistent IOP lowering in both previously treated and untreated patients with primary open-angle glaucoma or ocular hypertension. BTFC was associated with significant IOP reductions, good tolerability, and good compliance. Keywords: bimatoprost 0.03%, intraocular pressure, ocular hypotensive medication, prostaglandin analog, ß-blocker